Analisis Faktor Kepuasan Mahasiswa S1 UPH - -, Fardiansyah; Bernarto, Innocentius (JBE (Journal of Business and Economics); Volume 9 No.1, 2010 JBE UNKLAB, 2010)
This research discusses the six factors that influences student’s satisfaction in UPH The six factors used in this study are the campus, administration, teacher, information, the SLIM system, and facility. The research data was obtained by distributing questionnaires to 300 students from batch 2008 and 2009. Purposive sampling technique was used. The analysis method was exploratory factor analysis using SPSS software version 15.0. The  results of hypothesis testing in this study found out that administrative factor, lecturer factor, the factor of information, SLIM system factor and facility factor affecting students satisfaction in a particular class of batch 2008 and 2009 and that indicators in it should be noticed in providing service to students. Further research is expected to examine the students with different batches or S2 students so the result will be more general.